Keberadaan Asas Rebus Sic Stantibus dalam Perjanjian Internasional - Harry Purwanto (Mimbar Hukum - Fakultas Hukum Universitas Gadjah Mada, 2011)
This article aims to explore the dynamics of rebus sic stantibus principle in international treaty. How are experts perspective and international law regulate about this principle, and how the implementation of principle in international society. Rebus sic stantibus principle may be invoked as a ground for terminating or withdrawing or suspending the enactment of international treaty.  Tulisan ini menelaah dinamika asas rebus sic stantibus dalam perjanjian internasional. Bagaimana pandangan para ahli terhadap asas ini, bagaimana hukum internasional mengaturnya, dan bagaimana penerapan asas ini dalam kenyataannya di masyarakat internasional. Asas rebus sic stantibus dapat dijadikan sebagai dasar untuk mengakhiri atau menarik diri atau menunda atas berlakunya suatu perjanjian internasional.